Reputation: 442
This seems more of a direct question. I will generalize it a bit at the end.
I am trying to this function in numpy. I have been successful using nested for loops but I can't think of a numpy way to do it.
My way of implementation:
bs = 10 # batch_size
nb = 8 # number of bounding boxes
nc = 15 # number of classes
bbox = np.random.random(size=(bs, nb, 4)) # model output bounding boxes
p = np.random.random(size=(bs, nb, nc)) # model output probability
p = softmax(p, axis=-1)
s_rand = np.random.random(size=(nc, nc))
s = (s_rand + s_rand.T)/2 # similarity matrix
pp = np.random.random(size=(bs, nb, nc)) # proposed probability
pp = softmax(pp, axis=-1)
first_term = 0
for b in range(nb):
for b_1 in range(nb):
if b_1 == b:
continue
for l in range(nc):
for l_1 in range(nc):
first_term += (s[l, l_1] * (pp[:, b, l] - pp[:, b_1, l_1])**2)
second_term = 0
for b in range(nb):
for l in range(nc):
second_term += (np.linalg.norm(s[l, :], ord=1) * (pp[:, b, l] - p[:, b, l])**2)
second_term *= nb
epsilon = 0.5
output = ((1 - epsilon) * first_term) + (epsilon * second_term)
I have tried hard to remove the loops and use np.tile
and np.repeat
instead, in order to achieve the task. But can't think of a possible way.
I have tried searching google for finding exercises like such which can help me learn such conversions in numpy but wasn't successful.
Upvotes: 2
Views: 128
Reputation: 442
Maximally optimized code: (removal of first two loops is inspired from L.Iridium's answer)
squared_diff = (pp[:, :, None, :, None] - pp[:, None, :, None, :]) ** 2
weighted_diff = s * squared_diff
b_eq_b_1_removed = b.sum(axis=(3,4)) * (1 - np.eye(nb))
first_term = b_eq_b_1_removed.sum(axis=(1,2))
normalized_s = np.linalg.norm(s, ord=1, axis=1)
squared_diff = (pp - p)**2
second_term = nb * (normalized_s * squared_diff).sum(axis=(1,2))
loss = ((1 - epsilon) * first_term) + (epsilon * second_term)
Timeit track:
512 µs ± 13 µs per loop
Timeit track of code posted in question:
62.5 ms ± 197 µs per loop
That's a huge improvement.
Upvotes: 0
Reputation: 344
P_hat.shape
is (B,L), S.shape
is (L,L), P.shape
is (B,L).
array_before_sum = S[None,:,None,:]*(P_hat[:,:,None,None]- P_hat[None,None,:,:])**2
array_after_sum = array_before_sum.sum(axis=(1,3))
array_sum_again = (array_after_sum*(1-np.ones((B,B)))).sum()
first_term = (1-epsilon)*array_sum_again
second_term = epsilon*(B*np.abs(S).sum(axis=1)[None,:]*(P_hat - P)**2).sum()
Upvotes: 1
Reputation: 14399
I think you can do both with einsum
first_term = np.einsum('km, ijklm -> i', s, (pp[..., None, None] - pp[:, None, None, ...])**2 )
second_term = np.einsum('k, ijk -> i', np.linalg.norm(s, axis = 1), (pp - p)**2 )
Now there's a problem: that ijklm
tensor in first_term
is going to get huge if nb
and nc
get large. You should probably distribute it so that you get 3 smaller tensors:
first_term = np.einsum('km, ijk, ijk -> i', s, pp, pp) +\
np.einsum('km, ilm, ilm -> i', s, pp, pp) -\
2 * np.einsum('km, ijk, ilm -> i', s, pp, pp)
This takes advantage of the fact that (a-b)**2 = a**2 + b**2 - 2ab
to allow you to break the problem into three parts that can each be done in one step with the dot product
Upvotes: 0